Evidence agreement in commercial proceedings – between theory and practice (Discourse of Law and Administration, 2021)
The subject of this study is an attempt to evaluate the new procedural institution introduced by the largest amendment to the Polish civil procedure in recent years. It is a contract of evidence, which, in the opinion of the legislator, was to facilitate the course of the evidence proceedings and, consequently, speed up the examination of a business case. After almost two years of the amended regulations being in force, a natural question arises as to what extent the theoretical assumptions proved successful in the practical application of the law? The answer to the question will be preceded by a short analysis of the legislator’s assumptions, selected theoretical considerations and an indication of specific problems and doubts related to the practical use of the eponymous procedural mechanism.
Keywords: civil proceedings; commercial proceedings; entrepreneur; evidence proceedings; evidence agreement